Brand image and customers' willingness to pay a price premium for female's stitched clothing - Saad Munir; Asad Afzal Humayon; Munir Ahmed; Sajid Haider; Noor Jehan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The aim of the present study is to better understand customer's willingness to pay a price premium in the market for female's stitched clothing and what sort of brand images can be used by a brand in order to achieve price premium. This study is based on quantitative survey of brand images found in branding literature and their impact on customer's willingness to pay a price premium for branded female's stitched clothing. This study applies regression analysis to find out the strength of the role of brand image dimensions towards willingness to pay price premium, using data collected from 409 university level female students. The outcome of the present study demonstrates that perceived uniqueness is the strongest predictor, perceived social image is the second strongest, perceived corporate social responsibility is the third strongest predictor, perceived awareness is the fourth strongest predictor, perceived quality is the fifth strongest predictor, perceived country of origin is the last strongest predictor of customer's willingness to pay a price premium. This study looks into other branding related dimensions to check price premium rather than actual price premium determinants. The outcomes aid brand managers to be aware of the significance of incorporating price premium and to build up an improved perceptive of what brand images dimensions coerce price premium.
Keywords: 330; customer' willingness; price premium; brand image; perceived uniqueness; perceived social image; perceived corporate social responsibility; perceived awareness; perceived quality; perceived country of origin